Modulação da expressão da proteína XPA em resposta ao tratamento com azul de metileno fotossensibilizado - Silva, Acarizia Eduardo da (2010)
Reactive oxygen species (ROS) are produced by aerobic metabolism and react with biomolecules, such as lipids, proteins and DNA. In high concentration, they lead to oxidative stress. Among ROS, singlet oxygen (1O2) is one of the main ROS involved in oxidative stress and is one of the most reactive forms of molecular oxygen. The exposure of some dyes, such as methylene blue (MB) to light (MB+VL), is able to generate 1O2 and it is the principle involved in photodynamic therapy (PDT). 1O2 e other ROS have caused toxic and carcinogenic effects and have been associated with ageing, neurodegenerative diseases and cancer. Oxidative DNA damage is mainly repaired by base excision repair (BER) pathway. However, recent studies have observed the involvement of nucleotide excision repair (NER) factors in the repair of this type of injury. One of these factors is the Xeroderma Pigmentosum Complementation Group A (XPA) protein, which acts with other proteins in DNA damage recognition and in the recruitment of other repair factors. Moreover, oxidative agents such as 1O2 can induce gene expression. In this context, this study aimed at evaluating the response of XPA-deficient cells after treatment with photosensitized MB. For this purpose, we analyzed the cell viability and occurrence of oxidative DNA damage in cells lines proficient and deficient in XPA after treatment with MB+VL, and evaluated the expression of this enzyme in proficient and complemented cells. Our results indicate an increased resistance to treatment of complemented cells and a higher level of oxidative damage in the deficient cell lines. Furthermore, the treatment was able to modulate the XPA expression up to 24 hours later. These results indicate a direct evidence for the involvement of NER enzymes in the repair of oxidative damage. Besides, a better understanding of the effects of PDT on the induction of gene expression could be provided